-3(2a-3)=3(a-6)

Simple and best practice solution for -3(2a-3)=3(a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(2a-3)=3(a-6) equation:


Simplifying
-3(2a + -3) = 3(a + -6)

Reorder the terms:
-3(-3 + 2a) = 3(a + -6)
(-3 * -3 + 2a * -3) = 3(a + -6)
(9 + -6a) = 3(a + -6)

Reorder the terms:
9 + -6a = 3(-6 + a)
9 + -6a = (-6 * 3 + a * 3)
9 + -6a = (-18 + 3a)

Solving
9 + -6a = -18 + 3a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3a' to each side of the equation.
9 + -6a + -3a = -18 + 3a + -3a

Combine like terms: -6a + -3a = -9a
9 + -9a = -18 + 3a + -3a

Combine like terms: 3a + -3a = 0
9 + -9a = -18 + 0
9 + -9a = -18

Add '-9' to each side of the equation.
9 + -9 + -9a = -18 + -9

Combine like terms: 9 + -9 = 0
0 + -9a = -18 + -9
-9a = -18 + -9

Combine like terms: -18 + -9 = -27
-9a = -27

Divide each side by '-9'.
a = 3

Simplifying
a = 3

See similar equations:

| h+4=2h-19 | | z=3*x-y | | y=0.95x | | 9.2-x=7.3 | | -7x+y=-1 | | 3x-11=x-5 | | -3(2x-3)=3(x-6) | | 4x+3=2(2x+2)-2x | | y=0.75(4)x | | 4=-0.5x^2+46 | | 42=12+3p | | 31(2c+4)=2(c+6)+c | | 7[2e-1]-3=6+6e | | 32=7(n+7)+5(5n+3) | | Y+2=.6(x+4) | | 42=2.333333x | | 6x+34x=7 | | 10p-3=2[12+4p]-7 | | 800=2x+3x+10x | | 9g=3[-4+5g] | | 500=2x+8x | | Y=-.6x-1 | | 3j+10=-30 | | .13x+x=141 | | 4[3+c]+c=c+4 | | 400=2x+6x | | x^3+y^2+2y-4x=5 | | 3z^2-7x+2=0 | | 28=14+7x-42 | | 3x-2y+5z=16 | | 9(y+5)=y+45 | | 4[3+c]+4=c+4 |

Equations solver categories